Heat transfer and fluid flow around starfish-inspired cylinder by immersed boundary-simplified thermal lattice Boltzmann method - Ma, Yuan (Engineering analysis with boundary elements)
Nowadays, the demands of small component sizes and high performance of electronic systems cause the challenges of cooling systems. It is important to study the geometrical modifications of cooling devices to obtain high heat transfer performance. This study investigates the liquid motion and energy transfer structures around the starfish-inspired cylinder. The shape of the starfish-inspired cylinder is evolved from the circular cylinder by changing one parameter (tuber length) in the math formula. The numerical simulations are performed using new numerical scheme, which based on the boundary-simplified thermal lattice Boltzmann method (IB-STLBM). The effects of tuber length (2 ≤ m ≤ 4), angle of attack (0 ≤ θ ≤ 0.2π), and Reynolds number (40 ≤ Re ≤ 100) on the circulation patterns and energy transport characteristics are analyzed. In the process of changing considered parameters, five different structures can be obtained, namely, steady separated flow, unsteady trailing-edge separated flow, unsteady leading-edge separated flow, unsteady one-bubble separated flow and unsteady two-bubble separated flow. For the cases which are unsteady and asymmetrical, Cdmean, Cdrms, Clmean, Clrms, Numean and Nurms have a positive function of m. At Re = 40, Cdmean increases initially and decreases afterward with increasing θ. However, for Re = 70 or 100, Cdmean decreases, and Numean rises as the increment of θ. When Re = 40, there is one critical value of the angle of attack for reaching the largest value of Numean. As for Re = 70 or 100, the best heat transfer performance can be obtained at θ = 0.2π.